Interaction between Organic Production and Genetically Modified Organisms: European Regulatory Framework and Positions to Unification of National Legislation of Ukraine - Piddubnyi, Oleksii; Piddubna, Daria; Obiiukh, Nataliya (European Journal of Sustainable Development, 2019)
The determined global direction towards the development of organic farming has come to gain its support in each country. Ukraine is no exception here as the country which has chosen for itself the course on European integration and therefore it has taken on certain responsibilities. Among these issues it is possible to determine the ways to harmonization of national legislation. That process should be taken through careful study of European legal regulation as well as the practice in its application and the current positive or negative aspects, gaps, etc. Such a systematic approach will provide the opportunity to develop new laws to ammend the current legal acts that will maximally regulate the relevant social relations. The reason for the chosen direction of scientific research is that it is often dificult, and sometimes impossible, to combine organic production and activities with the use of genetically modified organisms. The research paper focuses on detailed characteristic of European legislation in the sphere of genetically modified organisms and analysing the general EU legal acts in the sphere of organic production. There are established the present provitions of national legislation and it is determined the structure of actions in order to support the development and spreading of organic farming in Ukraine. Keywords: organic production, organic farming, genetically modified organisms, unification, national legislation, European legal framework, scietific doctrine